Clinical Consideration of Anatomical Variations in the Common Hepatic Arteries: An Analysis using MDCT Angiography - Asim Ali, Khoala Riaz, Muhammad Ramzan, Muhammad Usman Younas, Abdullah Saeed, (Pakistan Journal of Medical & Health Sciences, 2023)
Purpose: The purpose of this study was to determine the prevalence of normal hepatic vascularization and variations in the common hepatic arteries using multidetector computer tomography angiography. These variants should be acknowledged before any surgery of the upper abdomen. The aim of our work was to analyze the variations in the hepatic arteries and their possible clinical and surgical implications. Materials and methods: This study was carried out on 4192 patients who underwent 64-slice MDCT angiography, from January 2020 to January 2023. We used surface and volume-rendering techniques in order to post-process images of the vascular components in the desired area. Results: We highlighted 76 cases with replaced common hepatic arteries, which are characterized by the origin of the common hepatic artery trunk located outside the classical composition of the celiac trunk. We identified three levels of origin: the abdominal aorta, the superior mesenteric artery and the left gastric artery. We observed six different aspects of the morphological variability of the celiac trunk and the superior mesenteric artery. The trajectory of the artery trunk, between the aortic origin and the hepatic pedicle portion of the hepatic portal vein, is variable and we analyzed the pancreatic trajectory accordingly. Conclusions: The prevalence of hepatic arterial variants found during this study was similar to that in other specialized studies. We came across variants that have not been described in the well known classification of Michels and even described extremely rare variations. The study of abnormal hepatic vascularization plays an important role in the surgical planning of hepatic transplantation, liver and pancreatic resection and extra hepatic upper abdominal surgeries. Keywords: hepatic artery; anatomical variations; multi detector computed tomography angiography